2022
DOI: 10.1590/1519-6984.256927
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compound and fatty acid properties of some microalgae species isolated from Erbil City

Abstract: The total phenolic compound and fatty acid profiles of lipids from microalgae are unique. The present study was designed to investigate aqueous, ethanolic and acetone extracts of several algae (Spirogyra sp., Spirulina sp.,Chlorella sp and Chara sp.) for their antioxidant capacities of the crude extracts and fractions by radical scavenging activity against the stable radical 1,1-diphenyl-2-picrylhydrazyl DPPH as well; total phenolic content. The results showed that Spirulina sp. indicated significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…was received from a microbiology lab and subcultured on BG11 media examined under a microscope to verify the algal. The morphological characteristics of the current study were similar to the Iraqi strains of Chlorella identified by [24] which confirmed the strain and shows MNPs (Figure 1).…”
Section: Chlorella Harvestingsupporting
confidence: 82%
“…was received from a microbiology lab and subcultured on BG11 media examined under a microscope to verify the algal. The morphological characteristics of the current study were similar to the Iraqi strains of Chlorella identified by [24] which confirmed the strain and shows MNPs (Figure 1).…”
Section: Chlorella Harvestingsupporting
confidence: 82%
“…Anwer and coauthor's isolated phenolic compound and fatty acid properties of some microalgae species and they found that microalgae with a high antioxidant capacity may be investigated for various industrial and pharmaceutical uses 22 .…”
Section: Resultsmentioning
confidence: 99%
“…The expressive antioxidant capacity of the bark of P. platycephala can be attributed to some compounds such as: (Z)-9-octadecenamide and octacosanol, are present in BEE, trilinolein is present in BME, and ferulic acid, caffeic acid, and 1,2,3-benzenetriol are present in both extracts. Anwer et al (2022) asserted that (Z)-9-octadecenamide is one of the representatives of fatty acids with relevant antioxidant capacity. Recent studies corroborate this perception (Emre and Kursat, 2022) through the application of bioinformatics methods aimed at predicting the pharmacokinetics of (Z)-9-octadecenamide.…”
Section: Discussionmentioning
confidence: 99%